MOBILE HEALTH APPLICATION UTILIZATION AND E-HEALTH LITERACY AMONG MEDICAL AND HEALTH STUDENTS - Julaeha Julaeha; Devi Solikhati (Jurnal Ilmiah Ibnu Sina (JIIS): Ilmu Farmasi dan Kesehatan, 2021)
Fast changing technology application in industry 4.0 technology era implicated on teaching and health services face to face paradigm to virtual services. Excellence health services influenced by good health literacy. The propose of this study is to evaluation knowledge, attitude, and practice medical and health students toward mobile health application and e-health literacy.The study adopted a descriptive cross sectional survey design was conducted in medical and health students in Indonesia during March-July 2020. An Indonesian Electronic Health Literacy Scale (IEHLS) was developed to evaluate Knowledge, Attitude, and Practice (KAP) about e-health literacy and mobile health apps among medical and health students. The full response rate was 99% (n=301). Half of respondents are mobile health apps active user (52.6%). Hallodoc apps was th e most mobile health apps used (60.5%), followed by Medscape (41.5%) and MIMS (23.6%). Diseases information, side effect, indication, and regimen dose of drugs were the most favourite information accessed among medical and health students. Around 80% of medical and health students agree that mobile health apps improve patient’s knowledge on their own disease and medication and helped healthcare professionals on giving education and counseling. In other hand, only 60% medical and health students agree mobile health apps might be use full in learning process and healthcare services. Knowledge, attitude, and practice medical and health students toward mobile health application will be elevated with improving level of health literacy.